2018
DOI: 10.1016/j.cogsys.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the mind. Why cultural theorists need the meme’s eye view

Abstract: Are there any such things as mind parasites? By analogy with biological parasites, such cultural items are supposed to subvert or harm the interests of their host. The hypothesis of cultural parasitism has appeared in different guises in the burgeoning field of cultural evolution. To unpack the notion of mind parasites, we first clear some conceptual ground around the concept of cultural adaptation and its relation to human agency. We then formulate Millikan's challenge: how can cultural items develop novel pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…14 Some have proposed that certain ideas or memes (in Dawkins's (1993) sense) should be understood as analogous to viruses in a more literal sense, in that they have purposes of their own, are shaped by (cultural) evolutionary processes, and their success in replicating comes at the expense of the host's interests (e.g. Boudry & Hofhuis, 2018). I'll set this question aside.…”
Section: Epistemic Inoculationmentioning
confidence: 99%
“…14 Some have proposed that certain ideas or memes (in Dawkins's (1993) sense) should be understood as analogous to viruses in a more literal sense, in that they have purposes of their own, are shaped by (cultural) evolutionary processes, and their success in replicating comes at the expense of the host's interests (e.g. Boudry & Hofhuis, 2018). I'll set this question aside.…”
Section: Epistemic Inoculationmentioning
confidence: 99%
“…Meme-theorists propose that we should look at our culture in a similar way. Culture also spreads through us, and is beneficial in most cases -our survival also depends upon our culture -but some forms of culture may 'behave' like deleterious parasites, spreading at the expense of their human hosts (Boudry & Hofhuis, 2018).…”
Section: Meme-theorymentioning
confidence: 99%
“…The studies of many authors have shown how the processes of globalization and fundamental changes in culture that affect the spiritual life of modern man are correlated. The idea appears in the work of S. Hofhuis [1].…”
Section: Introductionmentioning
confidence: 99%